Effects of Jianpi Bushen Therapy for Treatment of CKD Anemia: A Meta-Analysis of Randomized Controlled Trials - Liang Li; Chengyin Li; Yu Zhou; Qi Xu; Zilin Wang; Xiaoyun Zhu; Yuanming Ba; Yuanming Ba (Frontiers Media S.A., 2020)
ObjectivesTo evaluate the efficacy of Traditional Chinese Medicine, specifically Jianpi Bushen (JPBS) therapy, for treatment of patients with chronic kidney disease (CKD) anemia.MethodsRandomized controlled trials of JPBS therapy for CKD anemia were searched and selected from seven electronic databases. The Cochrane collaboration tool was used to conduct methodological quality assessment. RevMan v5.3 software was utilized to perform data analysis.ResultsIn total, 12 randomized controlled trials with 799 patients met the meta-analysis criteria. The aggregated results indicated that JPBS therapy is beneficial for CKD anemia by improving the clinical efficacy rate [risk ratio (RR) = 1.23, 95% confidence interval (CI): (1.14, 1.33), P < 0.00001] and hemoglobin (Hb) [weighted mean difference (WMD) = 9.55, 95% CI: (7.97, 11.14), P < 0.00001], serum ferritin (SF) [WMD = 6.22, 95% CI: (2.65, 9.79), P = 0.0006], red blood cell (RBC) [WMD = 0.31, 95% CI: (0.24, 0.38), P < 0.00001], hematocrit (HCT) [WMD = 2.95, 95% CI: (2.36, 3.54), P < 0.00001], serum creatinine (SCr) [WMD = 64.57, 95% CI: (33.51, 95.64), P < 0.0001], and blood urea nitrogen (BUN) levels [WMD = 3.76, 95% CI: (2.21, 5.31), P <0.00001]. Furthermore, evidence suggests that JPBS therapy is safe and does not increase adverse reactions compared with western medicine (WM) alone.ConclusionThis study found that JPBS therapy has a positive effect on the treatment of CKD anemia. However, more well-designed, double-blind, large-scale randomized controlled trials are needed to assess the efficacy of JPBS therapy in the treatment of CKD anemic patients.